Suppression of T-Cell Proliferation by Normal Density Granulocytes Led to CD183 Downregulation and Cytokine Inhibition in T-Cells - Julia Westerlund; Sandra Askman; Åsa Pettersson; Thomas Hellmark; Åsa C. M. Johansson; Markus Hansson (Journal of Immunology Research)
Normal density granulocytes (NDGs) can suppress T-cell responses in a similar way as myeloid-derived suppressor cells (MDSCs). In this study, we tested the hypothesis that NDGs from healthy donors preferentially inhibit T helper 1 (Th1) cells and investigated the myeloid-derived suppressive effect in different T-cell populations. We found that NDG-induced suppression of T-cell proliferation was contact dependent, mediated by integrin CD11b, and dependent on NDG-production of reactive oxygen species (ROS). The suppression was rapid and occurred within the first few hours of coculture. The suppression did not influence the CD8+/CD4+ ratio indicating an equal sensitivity in these populations. We further analyzed the CD4+ T helper subsets and found that NDGs induced a loss of Th1 surface marker, CD183, that was unrelated to ligand-binding to CD183. In addition, we analyzed the Th1, Th2, and Th17 cytokine production and found that all cytokine groups were suppressed when T-cells were incubated with NDGs. We therefore concluded that NDGs do not preferentially suppress Th1-cells. Instead, NDGs generally suppress Th cells and cytotoxic T-cells but specifically downregulate the Th1 marker CD183.